Generation Z's Health Information Avoidance Behavior: Insights From Focus Group Discussions - Chenjin Jia; Pengcheng Li (JMIR Publications, 2024)
BackgroundYounger generations actively use social media to access health information. However, research shows that they also avoid obtaining health information online at times when confronted with uncertainty. ObjectiveThis study aims to examine the phenomenon of health information avoidance among Generation Z, a representative cohort of active web users in this era. MethodsDrawing on the planned risk information avoidance model, we adopted a qualitative approach to explore the factors related to information avoidance within the context of health and risk communication. The researchers recruited 38 participants aged 16 to 25 years for the focus group discussion sessions. ResultsIn this study, we sought to perform a deductive qualitative analysis of the focus group interview content with open, focused, and theoretical coding. Our findings support several key components of the planned risk information avoidance model while highlighting the underlying influence of cognition on emotions. Specifically, socioculturally, group identity and social norms among peers lead some to avoid health information. Cognitively, mixed levels of risk perception, conflicting values, information overload, and low credibility of information sources elicited their information avoidance behaviors. Affectively, negative emotions such as anxiety, frustration, and the desire to stay positive contributed to avoidance. ConclusionsThis study has implications for understanding young users' information avoidance behaviors in both academia and practice.